Building value chains for indigenous fruits: Lessons from camu-camu in Peru - Blare, Trent; Donovan, Jason (Cambridge University Press, 2018)
Governments and NGOs have enthusiastically promoted value chains for lesser-known indigenous fruits in the pursuit of poverty reduction and other development goals. This paper examines experiences in Peru in building the value chain for camu-camu—a fruit native to the Amazon that is in the process of being domesticated. We look at interventions to build the chain, the environment in which the chain operates, the implications of chain development on livelihoods, and prospects for future chain development. Information was collected from gray literature as well as from primary data from household and key informant interviews. The results of this study suggest that the emergence of the camu-camu chain has led to higher farm income without generating large trade-offs in livelihood activities or the environment. However, the results also demonstrate an unrealized potential to achieve greater impact at scale due to gaps in services and inputs, limited coordination among farmers and chain actors, and a risky business environment. Building value chains for lesser-known fruits will require more than a techo-managerial focus on smallholder production. Greater attention is required to build stronger public–private collaboration to expand and diversify markets, with particular attention on strengthening institutions and growing local markets for high-value products.